Analisis Fasilitas di Area Keberangkatan terhadap Kepuasan Penumpang Bandar Udara Depati Amir Pangkalpinang - Pradana, Dirja Rizki; Riananditasari, Nanik (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
This research is motivated by the importance of airline companies in providing satisfaction to passengers through good and quality facilities. This study aims to determine the effect of facilities in the departure area on passenger satisfaction at Depati Amir Pangkalpinang Airport. The facilities in question include 4 indicators: facility conditions, completeness, interior design, and exterior design. The study was conducted using quantitative methods. Data were obtained by distributing Likert scale questionnaires with a sample size of 100 respondents. Sampling used purposive sampling technique, which is a sampling technique with certain criteria. The hypothesis was tested using simple regression and T-test. The results showed that there was a positive and significant effect on passenger satisfaction partially. As much as 92.7% of passenger satisfaction at Depati Amir Pangkalpinang Airport was influenced by facilities in the departure area. While the remaining 7.3% was influenced by other variables not studied.